Analysis Of Driving Stress Measured In The RC Long Pile - Yu Zhenquan (Deep Foundations Institute, 1991)
At the construction site of Bao Shan Iron &. Steel Mill in Shanghai, lots of RC driven piles with length of 50 to 60m were applied. The most unfavourable distribution of stress along the pile shaft was known by measuring the compressive and tensive stresses. With analysing the test results a phenomenon of impact fatigue of RC pile was discovered, the range of impact fatigue and its critical zone can be distinguished. Finally some countermeasures are presented to avoid the impact fatigue of RC long pile.